Peningkatan Kapasitas Kewirausahaan dan Digital Marketing untuk Anak Panti Asuhan Putri Baabussalaam Banyumas - Bagas Gumintang; Filda Khoirun Nikmah; Joni Prayogi; Ruby Faozan Qomaruzzaman (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2025)
This community service activity was carried out at the Baabussalaam Banyumas Foundation with the aim of improving the knowledge and entrepreneurial skills of orphanage children through enterpreneurship training and digital marketing. The program was attended by 15 foster children with an age range of 12-18 years. The implementation method includes the delivery of enterpreneurship materials, digitak marketing training, content creation practices, and technical assistance. The results of the activity showed a significant increase in the understanding of enterpreneurship concepts, skills in utilizing social media for promotion, and an increase in participants’ motivation and confidence. The orphanage’s flaghsip products in the form of pletok beer and ornamental plants have been successfully developed through more attractive packaging and simple digital promotion. This program received a positive response from participants and orphanage managers, and opened up sustainability opportunities through the formation of internal enterpreneurship groups. Thus, this training has proven to be a strategic solution to suppory the economic independence of orphanage children while supporting the development of the local creative economy.